Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1007/bf03161001
|View full text |Cite
|
Sign up to set email alerts
|

Binding of3H-progesterone by isolated rat islets of Langerhans

Abstract: Summary.Islets of Langerhans isolated from normal female rats have been used in studies of 3H-progesterone uptake by intact islet cells. The intracellular sites which are involved in binding of the hormones have been determined by subcellular fractionation and autoradiography. Uptake of 3H-progesterone into islets occurred in a temperature and concentration dependent manner. The uptake increased rapidly in the first 30 min, and could be partially displaced by addition of excess unlabelled progesterone. 3H-prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Sorenson et al demonstrated that progesterone counterregulates the effects of rat PRL on insulin secretion and B-cell proliferation of rat islets in a homologous in vitro system (22). The pancreatic B-cells in female rats are known to possess progesterone receptor (23,24). In the present study, the values of plasma progesterone remained relatively high during prolonged pregnancy and on day 19 of normal pregnancy.…”
Section: Discussionsupporting
confidence: 53%
“…Sorenson et al demonstrated that progesterone counterregulates the effects of rat PRL on insulin secretion and B-cell proliferation of rat islets in a homologous in vitro system (22). The pancreatic B-cells in female rats are known to possess progesterone receptor (23,24). In the present study, the values of plasma progesterone remained relatively high during prolonged pregnancy and on day 19 of normal pregnancy.…”
Section: Discussionsupporting
confidence: 53%
“…Progesterone treatment stimulated islet-cell proliferation in both intact male and female rats, although only female rats possess significant amounts of pancreatic progesterone receptors (2)(3)(4). Moreover, the effect of progesterone on islet-cell proliferation was absent in TX male and OVX female rats, suggesting that the gonads play an essential role in the genesis of the proliferative effect of progesterone.…”
Section: Discussionmentioning
confidence: 98%
“…In extra-islet pancreatic tissue of intact female rats, progesterone treatment Figure 4 shows a pancreatic section of an intact female rat, not treated with progesterone, doublestained for insulin and cytokeratin 20. In intact female rats not treated with progesterone, the incidence of cytokeratin 20/insulin double-immunoreactive cells in pancreatic tissue was 0.18Ϯ0.06 cells/mm 2 . In progesterone-treated female rats, this incidence was 0.31Ϯ0.10 cells/mm 2 (NS).…”
Section: Identification Of Proliferating Cellsmentioning
confidence: 92%
See 1 more Smart Citation
“…Several lines of experimental evidence lend sup port to such an assumption. Specific receptors for estro gen [27] and progesterone [9] have already been described, and a direct effect of glucocorticoids [5], estrogen [ 13], progesterone [13,14], thyroid hormones [28] and testosterone (unpublished data) have also been found. Furthermore, we can now report that the lack of three different steroid hormones, namely adrenal, female and male sexual hormones, differently and speci fically affects both insulin release and B-cell ultrastructurc.…”
Section: Discussionmentioning
confidence: 99%